Modern Trends and Factors of Financial Development of the Agricultural Sector in the Republic of Karakalpakstan, Taking Into Account Agricultural Insurance (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In accordance with Resolution of the Cabinet of Ministers of the Republic of Uzbekistan No. 119 dated March 4, 2017, a regulation was developed on an insurance partnership to insure the risk of non-repayment of loans allocated to owners of peasant farms and land plots, in accordance with which the Professional Association of Insurers without Legal Entity Status June 17, 2019 Cabinet The Ministers of the Republic of Uzbekistan adopted Resolution No. 505 “On improving the insurance system for the future harvest of raw cotton and grain crops with ears.”